Struktur Elemen Klausa Pada Bahasa Arab dan Bahasa Mongondow: Suatu Tinjauan Kontrastif - Miolo, Mukhtar I.; Mamonto, Muhammad Zaini; Habibie, Nurdias Ramadhan (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2025)
This study explores the clause structure in Arabic and Mongondow languages through a contrastive linguistic approach. Although originating from different linguistic families Arabic from the Semitic family and Mongondow from the Austronesian family both languages exhibit comparable syntactic patterns worth examining. This research employs a descriptive qualitative method with contrastive and content analysis techniques. Data were gathered from literature reviews and documentation of native speakers' utterances. The samples include various types of clauses: independent, dependent, verbal, nominal, adjectival, adverbial, and prepositional. The findings reveal fundamental similarities in clause structure between the two languages, particularly in the use of subject (S), predicate (P), and object (O). However, syntactic differences are identified, such as the use of ḥarf al-jarr (prepositions) in Arabic and the local preposition kon in Mongondow. Reflexive, reciprocal, and nominal clauses also display relatively consistent patterns across both languages. This study contributes to the development of comparative syntax and the preservation of regional languages. Furthermore, the findings offer practical insights for curriculum design, particularly in language education that integrates contrastive grammatical structures to enhance students’ understanding of interlingual differences in a systematic and contextual manner.